The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10815-018-1375-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the microfluidic chip technique in sperm selection for intracytoplasmic sperm injection for unexplained infertility: a prospective, randomized controlled trial

Abstract: Purpose The new-generation spermatozoon selection method, microfluidic technique called Fertile Chip ® gives the chance to select spermatozoa with lower DNA fragmentation indexes. We aimed to determine the effect of microfluidic techniques for spermatozoon selection in ICSI treatment in patients with unexplained infertility. Methods This prospective randomized controlled study was conducted at a university hospital. One hundred twenty-two couples with unexplained infertility were included, in which 61 of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 19 publications
5
51
3
Order By: Relevance
“…In our study, we tested whether sperm cells using the Fertile Plus chips create a difference compared with the gradient method in the selection of best sperms in terms of morphological and genomic integrity and success of pregnancy in microinjection (ICSI) cycles. A recent study comparing swim-up and microfluidic chip methods in IVF patients with unknown reasons reports that there was no difference between pregnancy and fertilisation rates [11]. In our study, we used gradient method instead of the swim-up method and we, too, failed to observe any difference between the two methods in pregnancy rates.…”
Section: Discussioncontrasting
confidence: 52%
“…In our study, we tested whether sperm cells using the Fertile Plus chips create a difference compared with the gradient method in the selection of best sperms in terms of morphological and genomic integrity and success of pregnancy in microinjection (ICSI) cycles. A recent study comparing swim-up and microfluidic chip methods in IVF patients with unknown reasons reports that there was no difference between pregnancy and fertilisation rates [11]. In our study, we used gradient method instead of the swim-up method and we, too, failed to observe any difference between the two methods in pregnancy rates.…”
Section: Discussioncontrasting
confidence: 52%
“…In the current literature, there is only one published study that reports the effects of using microfluidic chips for sperm selection in ICSI cycles compared with conventional swim‐up method among cases with unexplained infertility (Yetkinel et al, ). The data of this study showed that fertilisation rates were found to be comparable between groups; but, a number of grade 1 embryos were found to be significantly higher in microfluidic group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most important question whether their use is of any advantage in terms of laboratory and clinical IVF/ICSI outcomes still remains controversy. In the literature, there is only one study evaluating clinical data following the use of a commercial microfluidic chip (Fertile Plus ® ; Koek Biotechnology) for ICSI cycles who were suffering from unexplained infertility; they found that a number of grade 1 embryos were found to be significantly higher in microfluidic group resulting in a higher rate of embryo freezing despite comparable fertilisation ratios (Yetkinel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the novelty of these methodologies, there is only one study that employs the selected spermatozoa in ARTs. In a recent publication in which spermatozoa were selected from 122 patients with infertility of unknown etiology using a commercial microfluidic device (61 patients) (Fertile Chip ® , KOEK Biotechnology, Turkey) or by SU (61 patients), no differences were found in terms of fertilization, pregnancy, and live birth rates during ICSI between both sperm selection methods (Yetkinel et al, 2019). However, these authors observed a higher quality in those embryos produced with spermatozoa selected by Fertile Chip ® .…”
Section: Sperm Selection Based On Sperm Motility (Microfluidics)mentioning
confidence: 99%